Case Study On Toyota Motor Corporation - Masthan Ghani, Seeni Mohamed (2004)
This case study is intended to study comprehensively about the success of Toyota Motor Corporation (TMC), the second largest automaker in the world after General Motors Corporation (GM). In this paper also, through careful and systematic approach has identified a number of key strategic approaches that could be used by Toyota to gain extra competitive advantages and to ensure that the company's vision is fulfilled.